Clinical characteristics, management, and survival of retinoblastoma patients: a five-year study at an Indonesian tertiary eye hospital - Putri, Aliya Numasari; Kuntorini, Maya Sari Wahyu; Amiruddin, Primawita Oktarima (Paediatrica Indonesiana, 2024)
Background Studies on the clinical characteristics of retinoblastoma in Indonesia have been limited, even though retinoblastoma is the most common pediatric ocular malignancy worldwide and the second-most common pediatric malignancy in Indonesia. The estimated patient survival rate in lower-middle-income countries is 77%, and survival is highly dependent on early diagnosis and therapy. Objective To identify the clinical characteristics of retinoblastoma in patients at the Cicendo National Eye Hospital, as an Indonesian tertiary eye hospital. Methods This retrospective, observational study included pediatric patients <18 years of age diagnosed with retinoblastoma at the Cicendo National Eye Hospital, Bandung, West Java, between January 2018 and December 2022. We collected patients’ medical record data on age, gender, laterality, chief complaints, stage of disease, grouping, histopathologic features, therapy, and survival. Results Of 247 retinoblastoma patients (328 eyes) enrolled, 53.85% presented at 1-2 years of age and 50.61% were males. Patients mostly presented with unilateral (67.21%) retinoblastoma, leukocoria (51.82%) as the chief complaint, and classified as International Retinoblastoma Staging System (IRSS) stage III (33.20%). Tumors were mostly intraocular (58.84%), particularly group E (39.02%). Most tumors showed undifferentiated (45.43%) and high-risk features (54.27%). Most eyes were treated with combination therapy (74.09%), particularly local and systemic therapy (59.45%). Survival was noted at 18.62% of patients, but 62.75% of patients were lost to follow-up. Conclusion Most patients present with advanced retinoblastoma. Most histopathological results shows undifferentiated and high-risk features of the tumor. Delays in diagnosis and therapy may occur due to a lack of awareness and knowledge regarding clinical manifestations of retinoblastoma, which leads to worse prognosis.